2014
DOI: 10.1038/eye.2014.227
|View full text |Cite
|
Sign up to set email alerts
|

Association of choroidal thickness with eye growth: a cross-sectional study of individuals between 4 and 23 years

Abstract: Background and aims We aimed to evaluate the association of subfoveal choroidal thickness (SFCT) with age and to determine its relationship with axial length (AL) and ocular biometric parameters, in children and young adults during growth period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Similar studies carried out on children have also revealed an inverse correlation between ChT and axial length (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Original Research Articlementioning
confidence: 54%
“…Similar studies carried out on children have also revealed an inverse correlation between ChT and axial length (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Original Research Articlementioning
confidence: 54%
“…[2][3][4][5]7,12 In our study population of children, SFCT decreased by approximately 25 lm per millimeter increase in axial length (Table 2). In the study by Li and colleagues, 26 SFCT of young adults decreased by 58 lm for each millimeter increase in axial length.…”
Section: Discussionmentioning
confidence: 99%
“…Thicker SFCT was associated with older age and shorter axial length. 12 The Copenhagen Child Cohort 2000 Eye Study included 1323 healthy 11-and 12-year-old children and revealed a mean SFCT of 369 6 81 lm in girls and 348 6 72 lm in boys. 13 Longer axial length was associated with a thinner subfoveal choroid after adjusting for age and sex.…”
mentioning
confidence: 99%
“…In addition, for the relationship between choroidal thickness and gender, it has been reported that girls have higher choroidal thickness or choroidal volume than boys in some studies1920212430, although this did not reach statistical significance after adjusting for other related factors. However, one study found significantly thicker subfoveal choroidal thickness in boys than in girls29, while no relationship with gender was observed in other studies262731.…”
mentioning
confidence: 86%
“…The reasons for some of the contrary results obtained in previous studies may be due to the relatively small sample size2021222326273031, limited range of ages1925 or uneven proportions of refractive errors24. Thus, the purpose of this cross-sectional study is to investigate the characteristics of choroidal thickness and to explore the relationship between choroidal thickness and age in a large sample of normal Chinese school children aged 6 to 19 years with a wide range of refractive errors using SS-OCT.…”
mentioning
confidence: 91%